Opportunities to Address Specialty Care Deserts and the Digital Divide through the Veterans Health Administration's Telehealth Hub-and-Spoke Cardiology Clinic: Retrospective Cohort Study - Rebecca Lauren Tisdale; Colin Purmal; Neil Kalwani; Alexander Sandhu; Paul Heidenreich; Donna Zulman; Tanvir Hussain (JMIR Publications, 2024)
BackgroundTo address geographic barriers to specialty care access for services such as cardiology, the Veterans Health Administration (VA) has implemented a novel, regionalized telehealth care hub. The Clinical Resource Hub (CRH) model extends care, including cardiology services, to individuals in low-access communities across the region. Little is known, however, about the reach of such programs. ObjectiveThis study aimed to describe the initial CRH program implementation in terms of growth in users and clinical encounters, as well as the association between user characteristics and the use of CRH cardiology care, in VA's Sierra Pacific region (Northern California, Nevada, and the Pacific Islands). MethodsWe compared patients who used CRH cardiology services (CRH users) to those using non-CRH cardiology services (CRH nonusers) in the Sierra Pacific region between July 15, 2021, and March 31, 2023. After characterizing changes in the numbers of CRH users and nonusers and clinical encounters over the study period, we used multivariable logistic regression to estimate the association between patient-level factors and the odds of being a CRH user. ResultsThere were 804 CRH users over the study period, with 1961 CRH encounters concentrated at 3 main CRH sites. The CRH program comprised a minority of cardiology users and encounters in the region, with 19,583 CRH nonusers with 83,489 encounters. The numbers of CRH patients and encounters both increased at a steady-to-increasing rate over the study period, with increases of 37% (n=292 vs n=213) in users and 64% (n=584 vs n=356) in encounters in the first quarter of 2023 compared with the last quarter of 2022. Among CRH users, 8.3% (67/804) were female and 41.4% (333/804) were aged ≥75 years, compared with 4.3% (840/19,583) and 49% (9600/19,583), respectively, among CRH nonusers. The proportions of rural (users: 205/804, 25.5%; nonusers: 4936/19,583, 25.2%), highly disabled (users: 387/804, 48.1%; nonusers: 9246/19,583, 47.2%), and low-income (users: 165/804, 20.5%; nonusers: 3941/19,583, 20.1%) veterans in both groups were similar. In multivariable logistic models, adjusted odds ratios of using CRH were higher for female veterans (1.70, 95% CI 1.29-2.24) and lower for older veterans (aged ≥75 years; 0.33, 95% CI 0.23-0.47). Rural veterans also had a higher adjusted odds ratio of using CRH (1.19, 95% CI 1.00-1.42; P=.046). ConclusionsThe VA's Sierra Pacific CRH cardiology program grew substantially in its first 2 years of operation, serving disproportionately more female and rural veterans and similar proportions of highly disabled and low-income veterans compared to conventional VA care. This model appears to be effective for overcoming specialty care access barriers for certain individuals, although targeted efforts may be required to reach older veterans. While this study focuses on a single region, specialty, and health care system, lessons from implementing regionalized telehealth hub models may be applicable to other settings.